Latex agglutination test for field diagnosis of haemorrhagic septicaemia - Lily Natalia (Indonesian Center for Animal Research and Development (ICARD), 2001)
Pasteurella multocida is bacterial pathogens that cause haemorrhagic septicaemia (HS) in cattle and buffaloes. Various tests have been used to differentiate types of P. multocida, as well as to diagnose this specific disease. A latex agglutination test has been developed for the detection of P. multocida B:2 which is the causal agent of HS. This test is a rapid and simple test suitable for local laboratorium to diagnose HS cases in the field. A heat stable antigen consisting of mainly lipopolysaccharide (LPS) extract of formalin killed P. multocida 0019 was used to produce specific antibody against P. multocida B:2. The antiboy was then used to sensitise latex particles. Latex agglutination test have been used to screen some P. multocida field isolates and this test have been proven to be specific, simple and easy to be used in detecting P. multocida B:2. The specificity is due to antibodies recognising LPS or LPS protein complexes. Sensitised latex was stable at 4° C for at least12 months. This test should be used as an aid to diagnosis and employed principally to confirm and support clinical and post mortem findings of HS. Keywords: Pasteurella multocida B:2, haemorrhagic septicaemia (HS), diagnosis, latex agglutination test